Pengaruh Motivasi Kerja dan Komitmen Organisasional terhadap Kepuasan Kerja pada Perawat Rumah Sakit Umum Daerah Bobong - Mus, Anggita; Koesmono, Teman; Wulani, Fenika (Kajian Ilmiah Mahasiswa Manajemen, 2017)
This study aims to determine the effect of work motivation and organizational commitment to job satisfaction nurses Bobong Hospital. This research is a causal research. The entire population in the study was used as a sample (census study). Data were collected through questionnaires and then processed by multiple regression analysis technique using SPSS program. The object of this research is nurses Bobong Hospital. The number of samples used in this study amounted to 68 respondents. The result of this research is work motivation have an effect on signifikan to job satisfaction. Hence hypothesis 1 is fulfilled. In addition, other results indicate that organizational commitment has no effect on job satisfaction. Thus the 2nd hypothesis is rejected.